"I Don't Think I Would Have Recovered": A Personal and Sociocultural Study of Resilience among US Marines. (July 2015) - Marcellino, William M.; Tortorello, Frank
Ethnographic research among US Marines shows resilience is in their practices, not biology. Empirical evidence supports our claim that a personal-social understanding of resilience has superior explanatory power and plausibility over mechanistic and reductive frameworks that treat resilience as automated functions of human biopsychological systems. Marines dynamically pursue their values in context, and this resilience can only be defined in local, variable context, not globally and generally. USMC resilience training should focus on skills and concepts needed to resolve challenges to values in the lives of Marines. Technical-medical interventions should be reserved for clinical populations.